The effect of volatile anesthetics on cellular responses in the microcirculation of free tissue transfers - Szrama, Jakub; Kusza, Krzysztof; Sobczyński, Paweł; Molnar, Zsolt; Siemionow, Maria (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2022)
The purpose of this review was to summarize the anti-inflammatory and immunosuppressive properties of volatile anesthetics and present their potential impact on the outcomes of major surgical procedures as well as microsurgical cases of free tissue transfer. Inhaled anesthetics are commonly used as a component of general anesthesia in interventional procedures, reconstructive surgery, free tissue transfers and transplantation. Experimental and clinical studies have shown that volatile anesthetics such as halothane, sevoflurane, isoflurane or desflurane can affect the immune system of patients exposed to general anesthesia. In patients with no serious systemic diseases, this effect is transient and mostly clinically irrelevant. However, in patients subjected to the inflammatory response due to the active disease, cardiac or pulmonary failure or advanced age, the prognosis may improve or worsen following inhalation anesthesia depending on the type of systemic pathology. The available data from reported clinical trials, as well as the in vitro and in vivo experimental studies, have often reported conflicting statements regarding the impact of inhalation anesthetics on outcomes of surgical procedures. These differences may be due to the heterogeneity of the evaluated patients, the extent and duration of surgical procedures, and different experimental design and methodologies applied for assessment of the reported clinical and research studies. In this review, based on the available literature reports we have summarized the anti-inflammatory and immunosuppressive effects as well as cellular responses of inhalation anesthetics at the microcirculatory level and discussed their potential clinical implications for the outcomes of surgical procedures of free tissue transfers.